Identities through fashion : a multidisciplinary approach - González, Ana Marta, 1969- (Berg Publishers, 2012)
"With the triumph of a fashion milieu in which once tightly fixed rules have been deconstructed and most anything goes, fashion has become a fertile field of study for academics across disciplines. This volume thus intends to bring together academics from various disciplines - philosophy, sociology, medicine, anthropology, psychology and psychiatry - to examine fashion's complex relationship with post-industrial societies. Herein the authors seek to address, from the standpoint of their respective disciplines, what crucial functions fashion is fulfilling in the modern world, especially as it relates to the construction and deconstruction of the self. This volume is the result of an Experts Meeting held by the Social Trends Institute at which the authors presented original papers that were then revised in light of the meeting discussion. The Social Trends Institute is a non-profit research center that offers institutional and financial support to academics in all fields who seek to make sense of emerging social trends and their effects on human communities. STI focuses its research on four subject areas: family, bioethics, culture and lifestyles, and corporate governance"--